UPAYA PENINGKATAN PEMBELAJARAN SEPAK BOLA MENGGUNAKAN MODIFIKASI PERMAINAN GOL INJAK KELAS V SEMESTER II SD NEGERI 3 LANGENHARJO KEC. KENDAL KAB. KENDAL TAHUN 2013 (Department of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study is to determine the improvement of learning outcomes through the media game goal penjasorkes stomp on fifth grade students of SDN 3 Langenharjo District of Kendal Kendal. Research conducted using action research methods class with a time of research carried on in cycles 1 and 2 with the research procedures of planning, action, and reflection. Data collection techniques such as gathering information, of information about the cognitive, affective, psychomotor. The research instrument used, lesson plans, observation sheet, students, and test performance, data analysis using value analysis test. Based on the results of the study showed indications of improvement based on the learning process of expert assessment sheets and teacher observation penjasorkes, and pieces of student assessment showed good results with a success rate of 67% in the first cycle and second cycle 92% of the thoroughness with KKM 75. Judging from the results of the first cycle and the second increase reaching 25% stated already showed a high increase in learning. Based on the above data it can be concluded learning through play football stampede goal has succeeded in improving student learning outcomes.